2020
DOI: 10.1002/kjm2.12275
|View full text |Cite
|
Sign up to set email alerts
|

Cure or curd: Modification of lipid profiles and cardio‐cerebrovascular events after hepatitis C virus eradication

Abstract: Hepatitis C virus (HCV) eradication deteriorates lipid profiles. Although HCV eradication may reduce the risk of vascular events as a whole, whether deteriorated lipid profiles increases the risk of cardio‐cerebral disease in certain patients is elusive. Serial lipid profiles were measured before, during, at and 3 months after the end of direct‐acting antivirals (DAAs) therapy, and annually thereafter in chronic hepatitis C patients who achieved a sustained virological response (SVR, undetectable HCV RNA at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…For patients without a history or risk of cardiovascular complications, lipid-lowering agents might be held for 8-12 weeks with close monitoring of serum lipid profiles for potential lipid rebound and risk of significant cardiovascular events. 41 Several PPIs are categorized as having orange-category DDIs to SOF/LDV, SOF/VEL, and SOF/VEL/VOX due to pH-dependent solubility issues. In accordance with the prescribing information, SOF/LDV and SOF/VEL/VOX can be administered simultaneously with a lowdose PPI (defined as daily dose comparable to 20 mg of omeprazole or lower).…”
Section: Discussionmentioning
confidence: 99%
“…For patients without a history or risk of cardiovascular complications, lipid-lowering agents might be held for 8-12 weeks with close monitoring of serum lipid profiles for potential lipid rebound and risk of significant cardiovascular events. 41 Several PPIs are categorized as having orange-category DDIs to SOF/LDV, SOF/VEL, and SOF/VEL/VOX due to pH-dependent solubility issues. In accordance with the prescribing information, SOF/LDV and SOF/VEL/VOX can be administered simultaneously with a lowdose PPI (defined as daily dose comparable to 20 mg of omeprazole or lower).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 617 patients suggested that an low-density lipoprotein surge >40% during the follow-up period of 26.8 months (range: 1-65 months) was associated with development of cardio-cerebral vascular diseases. 59 Further work suggested that a combination of an increased small-dense lowdensity lipoprotein, which purportedly has greater atherogenic potential, and liver steatosis, as measured by elastographic CAP in SVR patients after DAAs, is associated with a potential synergistic risk on atherosclerosis. 51 Additionally, various studies highlighted an increase in hepatic steatosis after SVR.…”
Section: Are S Vr P Opul Ati On S V Ulner Ab Le To Mafld -Neg Ativementioning
confidence: 99%
“…Although, it is well established that HCV eradication reduce cardio‐cerebral vascular risk, 54‐58 some special subpopulation might be maintained at higher risk. A recent study of 617 patients suggested that an low‐density lipoprotein surge >40% during the follow‐up period of 26.8 months (range: 1‐65 months) was associated with development of cardio‐cerebral vascular diseases 59 . Further work suggested that a combination of an increased small‐dense low‐density lipoprotein, which purportedly has greater atherogenic potential, and liver steatosis, as measured by elastographic CAP in SVR patients after DAAs, is associated with a potential synergistic risk on atherosclerosis 51 …”
Section: Are Svr Populations Vulnerable To Mafld‐negative Impact?mentioning
confidence: 99%
“…Meanwhile, increase in total cholesterol and low‐density lipoprotein cholesterol (LDL‐C) have been reported in the post‐SVR phase. An LDL‐C surge of >40% occurring after HCV eradication was associated with increased risks of vascular events, urging more caution and research in this phenomenon 25 …”
Section: Unmet Needs Of Chronic Hepatitis C (Chc) Management In the Dmentioning
confidence: 99%